Demand Response Driven Load Pattern Elasticity Analysis for Smart Households - Paterakis, N. G.; Catalao, J. P. S.; Tascikaraoglu, A.; Bakirtzis, A. G.; Erdinc, O. (IEEE, 2015)
The recent interest in smart grid vision enables several smart applications in different parts of the power grid structure, where specific importance should be given to the demand side. As a result, changes in load patterns due to demand response (DR) activities at end-user premises, such as smart households, constitute a vital point to take into account both in system planning and operation phases. In this study, the assessment of the impacts of pricing based DR strategies on smart household load pattern variations is provided. The household load data sets are acquired from a provided model of a smart household, including appliance scheduling. Then, an artificial neural network (ANN) approach based on Wavelet Transform (WT) is employed for the forecasting of responsive residential load behaviors to different pricing schemes. From the literature perspective this study contributes by considering DR impacts on load pattern forecasting, being a very useful tool for market participants such as aggregators in future pool-based market structures, or for load serving entities to discuss potential change requirements in existing DR strategies, or even to effectively plan new ones.
Keywords: Air conditioner; Appliance Scheduling; Electric Vehicle; Electric Water Heater; Shiftable Appliances; Smart Home; SIDE MANAGEMENT; SYSTEM; Energy & Fuels; Engineering